Investigation of the influence of fodder vitamin-mineral concentrate on quality, safety and nutrition value of beef when feeding bulls - R. V. Kazaryan; M. V. Lukyanenko; A. S. Borodikhin; A. A. Fabritskaya; E. Y. Panasenko (Новые технологии, 2017)
The aim of the study is to study the effect of vitamin-mineral fodder concentrate on the quality, safety and nutritional value of beef.